Cyber-Based Defense Technology Development of the Six-ware Cyber Framework to Enhance the Implementation of the National Defense System in the City of Bata - R A G Gultom, A Farid, A A Lestari, C A S Lahallo, R N Akbar (International Journal of Advanced Science and Technology, 2020)
This paper presents the research on the "six-ware cybersecurity framework" approach to understanding its implementation that suits the characteristics of the Indonesian companies. The study makes use of the mixed method: survey and inferential statistical approach. Data collection was carried out at five loci in the city of Batam with 80 questionnaire respondents, and five subject matter experts from each locus. The results of this study indicate that "six-ware defence cyber framework" is suitable to be applied in the Indonesian companies. The qualitative interpretation shows the results of the matched patterns method, while quantitative results show that 85% of the factors can be responded to by the company at the locus. The results show that the framework has the advantage of the ease of implementation in measuring the company’s readiness against cyber threats